Deaths, Interventions, Humanitarianism and Human Rights in the Mediterranean 'Migration Crisis'. Issue 2 (3rd May 2016) - Perkowski, Nina
Abstract: Recent declarations of 'crises' in the Mediterranean have been distinctly humanitarian, being linked to human deaths and suffering. The growing emphasis on humanitarianism and human rights has coexisted with a continued security rationale, as the three discourses work together in the governance of EUrope's borders and in ongoing struggles over movement and control.